2020
DOI: 10.20944/preprints202005.0518.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Extracellular Vesicles to Global Environment: A Cosmopolite SARS-Cov-2 Virus<strong> </strong>

Abstract: Within the micro and nano world, tiny membrane-enclosed bits of material are more or less free to move and act as communication tools within cells, between cells, between different tissues and between organisms in global environment. Based on the mechanism of membrane budding and vesiculation that includes all types of cells, in this review, we attempted to present a review on SARS-CoV-2 virus actions in compartments of different scales (cells and their surroundings, tissues, organisms and society). Interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 148 publications
(194 reference statements)
0
3
0
Order By: Relevance
“…The SARS virus specifically binds to protein S, an enzyme that converts angiotensin 2 (ACE2). The enzyme ACE2 is found on cell membranes and serves as an entry port for the virus into the host cell (Koren et al, 2021;Kralj-Iglič et al, 2020). In a docking study, it was found that limonene could bind to ACE2 and potentially prevent the virus from entering cells (Abdelli et al, 2021).…”
Section: Limonene and Sars-cov-2 Virusmentioning
confidence: 99%
“…The SARS virus specifically binds to protein S, an enzyme that converts angiotensin 2 (ACE2). The enzyme ACE2 is found on cell membranes and serves as an entry port for the virus into the host cell (Koren et al, 2021;Kralj-Iglič et al, 2020). In a docking study, it was found that limonene could bind to ACE2 and potentially prevent the virus from entering cells (Abdelli et al, 2021).…”
Section: Limonene and Sars-cov-2 Virusmentioning
confidence: 99%
“…Material deposited also on the top surface of the TiO 2 nanotube walls is denoted by a black arrow. Adapted with permission from [ 60 , 61 ].…”
Section: Interaction Of Cells With Nanostructured Surfacesmentioning
confidence: 99%
“…In the case of electrochemical anodization, nanotubes with a diameter of 100 nm were synthesized by using HF and ethylene gylcol as electrolytes (described in detail in Refs. [ 60 , 61 ]), whereas for the hydrothermal method, Ti foils were exposed to a basic medium of Ti isopropoxide suspension. Briefly, in the hydrothermal method, Ti foil (0.1 mm, 99.6+%, Advent) was washed in acetone, ethanol, and water (in each for 5 min).…”
Section: Interaction Of Cells With Nanostructured Surfacesmentioning
confidence: 99%